Immunohistochemistry of resorption and inflammation factors in the periodontal ligament of human deciduous teeth - Bianca Zimmermann dos Santos; Rafael Cypriano Dutra; Adair Roberto Soares dos Santos; Maísa Casarin; Eliane Maria Goldfeder; Vera Lucia Bosco; Mabel Mariela Rodriguez Cordeiro (Sociedade Brasileira de Pesquisa Odontológica, 2022)
Abstract: The understanding of the biological mechanisms involved in root resorption in deciduous teeth is important to the future development of preventive measures and treatments of this condition. The aim of the present study was to compare the expression and immunostaining of iNOS, MMP-9, OPG and RANKL in the periodontal ligament (PDL) of deciduous teeth with physiologic root resorption (GI), inflammatory pathological root resorption (GII) and permanent teeth (GIII), the negative control. Teeth in GI (n = 10), GII (n = 10) and (GIII) (n = 10) were submitted to immunohistochemical analysis to determine the expression of iNOS, MMP-9, OPG, and RANKL. The immunostaining was analysed by optical density. Statistical analysis included one-way ANOVA, followed by Student-Newman-Keuls post hoc test (p < 0.05). The results showed that iNOS, MMP-9 and RANKL expression in the PDL was higher in GII compared to GI and GIII (p < 0.05). Moreover, RANKL expression was higher in GI compared to GIII (p < 0.001), while OPG immunolabelling was lower in GII compared to GI and GIII (p < 0.001). The PDL of deciduous teeth bearing inflammatory processed exhibited upregulation of resorption-associated factors as well as enzymes related to tissue degradation which, in turn explains the exacerbation and greater susceptibility of those teeth to root resorption process.